2017
DOI: 10.5603/cj.a2016.0087
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of beta-catenin in cardiomyocytes suppresses survival protein expression but promotes apoptosis and fibrosis

Abstract: (Cardiol J 2017; 24, 2: 195-205)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…β-catenin has been used as a marker of EMT in a number of studies of embryonic development, cancer, and fibrosis ( 30 33 ). According to previous studies, β-catenin is associated with EMT during renal fibrosis ( 34 ) and fibrosis in other organs ( 35 , 36 ). In addition, β-catenin participates in the development of PF by transforming A549 cells into fibroblasts ( 23 , 37 ).…”
Section: Discussionmentioning
confidence: 86%
“…β-catenin has been used as a marker of EMT in a number of studies of embryonic development, cancer, and fibrosis ( 30 33 ). According to previous studies, β-catenin is associated with EMT during renal fibrosis ( 34 ) and fibrosis in other organs ( 35 , 36 ). In addition, β-catenin participates in the development of PF by transforming A549 cells into fibroblasts ( 23 , 37 ).…”
Section: Discussionmentioning
confidence: 86%
“…Our earlier studies have shown that abnormal activation of IGF-IIR signaling pathway during cardiac stresses such as elevated Ang II levels [3], or high glucose [5], or drug-induced (doxorubicin) cardiotoxicity [12,13] could lead to increased hypertrophy, fibrosis, and cardiac apoptosis paving the way for heart failure. Besides, we showed that enhancement of β-catenin in cardiomyocytes promotes apoptosis and fibrosis during cardiac stresses such as myocardial infarction (MI) or diabetes [14]. This study showed that Ang-II treatment could upregulate β-catenin expression in parallel with IGF-IIR expression in a dose-dependent assessment.…”
Section: Discussionmentioning
confidence: 98%
“…In skeletal muscle tissue, nuclear β‐catenin has been shown to be upregulated in response to mechanical overload, which was mediated via the canonical Wnt/β‐catenin pathway 44 . Overexpression of cardiac β‐catenin was associated with cardiac hypertrophy, with increased fibrosis and with apoptosis in vitro 45,46 47 .…”
Section: Discussionmentioning
confidence: 99%